Cow's milk provocation induces an immune response to unrelated dietary antigens. - Suomalainen, H (1992)
The activation of immune mechanisms was evaluated by the solid phase enzyme linked immunoassay of immunoglobulin and specific antibody secreting cells in 27 patients (aged from nine to 69 months), subjected to a diagnostic cow's milk challenge or a rechallenge. A significant rise in the total number of immunoglobulin secreting cells was associated with clinically positive (n = 17), but not a negative (n = 10) cow's milk challenge in all immunoglobulin isotypes. The number of specific antibody secreting cells against beta lactoglobulin, mean (95% confidence interval), increased from 4.8 (1.4, 15.8) to 16.9 (5.5, 52.7) specific antibody secreting cells/10(6) cells, p = 0.02, and against casein from 2.2 (0.8, 6.1) to 7.5 (2.5, 22.5) specific antibody secreting cells/10(6) cells, p = 0.01, in patients positive to challenge in the IgM class only, indicating defective immune elimination of milk antigens. In addition to the specific immune response to cow's milk antigens, an increase in IgM specific antibody secreting cells against an unrelated dietary antigen, gliadin, from 8.2 (2.1, 31.1) to 31.0 (14.2, 67.6) specific antibody secreting cells/10(6) cells, p = 0.01, was observed. These results indicate that cow's milk challenge, in patients who have cow's milk allergy, induces a strong non-antigen specific immune response that includes a response against unrelated antigens concomitantly present in the intestinal lumen. Activation of such immune mechanisms may hence reflect increased antigenic load caused by the immune mediated lesion in the gut mucosa.